Automation of 3D Cell Culture Using Chemically Defined Hydrogels. (April 2014) - Rimann, Markus; Angres, Brigitte; Patocchi-Tenzer, Isabel; Braum, Susanne; Graf-Hausner, Ursula
Drug development relies on high-throughput screening involving cell-based assays. Most of the assays are still based on cells grown in monolayer rather than in three-dimensional (3D) formats, although cells behave more in vivo –like in 3D. To exemplify the adoption of 3D techniques in drug development, this project investigated the automation of a hydrogel-based 3D cell culture system using a liquid-handling robot. The hydrogel technology used offers high flexibility of gel design due to a modular composition of a polymer network and bioactive components. The cell inert degradation of the gel at the end of the culture period guaranteed the harmless isolation of live cells for further downstream processing. Human colon carcinoma cells HCT-116 were encapsulated and grown in these dextran-based hydrogels, thereby forming 3D multicellular spheroids. Viability and DNA content of the cells were shown to be similar in automated and manually produced hydrogels. Furthermore, cell treatment with toxic Taxol concentrations (100 nM) had the same effect on HCT-116 cell viability in manually and automated hydrogel preparations. Finally, a fully automated dose-response curve with the reference compound Taxol showed the potential of this hydrogel-based 3D cell culture system in advanced drug development.